Gender representation in government-endorsed Arabic language textbooks: Insights from Indonesia - Kuraedah, St; Gunawan, Fahmi; Alam, Samsu; Ubaidillah, M. Faruq; Alimin, Alimin; Fitriyani, Fitriyani (Frontiers in Education, 2023)
Although research on gender representation in textbooks has been carried out, Arabic textbook research is still lacking. To fill this gap, this study aims to examine gender representation in Arabic textbooks for Islamic high school students approved by the Ministry of Religion of Indonesia. This research employed a case study design focusing on three textbooks. The researcher utilized thematic analysis anchored in Rifkin’s theory. The findings show that gender representation in Arabic textbooks verbally and visually is dominated by men. Gender representation visualized from six themes shows male dominance except for the theme "travelling” is dominated by women. (3) The pedagogical actions that need to be taken to overcome these problems are: (a) Arabic language teachers need to develop materials when using government-endorsed Arabic textbooks, b) The Ministry of Religion should promote gender equality through recommended textbooks.